Sexual dysfunctions of rheumatological patients are a neglected issue: Results from a national survey of Italian Society of Rheumatology - Luigi Napolitano; Ilenia Pantano; Lorenzo Romano; Luigi Cirillo; Celeste Manfredi; Francesco Matrangelo; Giovanni Maria Fusco; Daniele Mauro; Lorenzo Spirito; Roberto La Rocca; Davide Arcaniolo; Corrado Aniello Franzese; et al. (Archivio Italiano di Urologia e Andrologia, 2023)
Introduction: Sexual dysfunctions (SD) are frequently encountered in patients with rheumatologic diseases. In this scenario, a multidisciplinary approach to rheumatologic diseases is often mandatory. The aim of this survey was to assess whether Italian rheumatologists routinely explore sexual health of their patients, their knowledge on the topic, and the barriers to discussing SD in clinical practice. Methods: A 32-items anonymous questionnaire was mailed to members of the Italian Society of Rheumatology (rheumatologists and residents in rheumatology training) in February 2023. The questionnaire aimed to determine attitudes, knowledge, and practice patterns regarding the discussion of SD with rheumatologic patients. A descriptive analysis of responses was performed. Results: A total of 162 responses were received. Overall, 50.0% of respondents occasionally asked patients about SD related to their rheumatologic pathologies, while 37.1% never did so. Respondents declared that patients occasionally (82.3%) or never (16.1%) reported SD related to rheumatologic diseases. The main barriers to discussing sexual health were lack of time during medical examination (46.6%), patients’ discomfort (44.8%), and lack of knowledge/experience (39.7%). Overall, 41.9% and 33.9% of respondents respectively totally and partially agreed that rheumatologists should routinely investigate patients' sexual health. Most of the respondents (79.0%) thought that discussing sexual health problems could help patients cope with their rheumatologic diseases. Of all respondents, 74.2% felt the need to broaden their personal knowledge about SD. Finally, 45.9% and 34.4% of respondents respectively partially and totally agreed that training courses for rheumatologists could be helpful in the management of sexual health in rheumatological patients. Conclusions: SD was not routinely discussed in rheumatology practice, still remaining a neglected issue. The most frequent explanations for the lack of attention toward SD were lack of time, patients’ discomfort, and lack of knowledge/experience. Most of the respondents expressed the possible usefulness of attending SD courses to improve knowledge about these conditions.